Deep Sea Actinomycetes and Their Secondary Metabolites - Kamjam, Manita; Sivalingam, Periyasamy; Deng, Zinxin; Hong, Kui (Frontiers in Microbiology, 2017)
Deep sea is a unique and extreme environment. It is a hot spot for hunting marine actinomycetes resources and secondary metabolites. The novel deep sea actinomycete species reported from 2006-2016 including 21 species under 13 genera with the maximum number from Microbacterium, followed by Dermacoccus, Streptomyces and Verrucosispora, and one novel species for the other 9 genera. Eight genera of actinomycetes were reported to produce secondary metabolites, among which Streptomyces is the richest producer. Most of the compounds produced by the deep sea actinomycetes presented antimicrobial and anti-cancer cell activities. Gene clusters related to biosynthesis of desotamide, heronamide and lobophorin have been identified from the deep sea derived Streptomyces.